A new scholarship of classroom-based, open, communal inquiry - Parker, Jan (Teaching and Learning Inquiry, 2013)
This article argues that SoTL may draw on and inform other scholarships—of discovery, application and integration—by bringing them into a classroom- and community-based scholarship of communal inquiry. In so doing, SoTL will resist teaching being regarded and evaluated as transmission and delivery of knowledge made elsewhere, reasserting the classroom as the place for the development of knowledge- and meaning-making, the site and focus of ‘teaching-led research’. It outlines a scholarship of communal inquiry which includes students, community and academics, as well as ‘Discovery’ and Teaching and Learning scholars: a boundary-crossing community creating, evaluating and publishing disciplinary knowledge, including from open data and curriculum- and assessment-change processes. Further, that a scholarship of inquiry that is developed in partnership with community interest groups (through scholarship of application projects), ground-ing and re-valuing the research agenda of higher institutes and professions while reimaging the curriculum, will prepare the student to become that lifelong, practitioner-scholar so needed for our future.